2012
DOI: 10.1590/s1516-35982012000500015
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative cooling for lactating sows under high ambient temperature

Abstract: -Two experiments were conducted to evaluate the evaporative cooling of the air at farrowing on the performance of lactating sows under high environmental temperature conditions in the Central West region of Brazil. One hundred and forty-four lactating sows -46 of first and second farrowing (experiment I) and 98 from the third to eighth farrowing (experiment II) -were used. Sows were distributed in experimental design of randomized blocks consisting of two rooms (with air cooling and control), with the sow as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
1
9
0
2
Order By: Relevance
“…All others reported an increase in this variable (kg d -1 ) with the use of the evaporative cooling system. This increase varied from 0.40 kg d -1 (MORALES et al, 2013) to 1,67 kg d -1 (KIEFER et al, 2012), the latter observed in primiparous sows ( Table 6).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…All others reported an increase in this variable (kg d -1 ) with the use of the evaporative cooling system. This increase varied from 0.40 kg d -1 (MORALES et al, 2013) to 1,67 kg d -1 (KIEFER et al, 2012), the latter observed in primiparous sows ( Table 6).…”
Section: Resultsmentioning
confidence: 88%
“…In 54% of the studies, the effect of the evaporative cooling system on pregnancy and / or lactation on some piglet-related variable was evaluated. From these parameters, piglet weight at weaning was the most influenced and showed improvement of up to 22% for lactating sows (parity one and two) when submitted to the cooling system (KIEFER et al, 2012). Differences in mortality of piglets with the use of cooling were not observed ( Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Kiefer et al (2012) também não encontraram diferença significativa no número de leitões desmamados ou mortalidade ao desmame para porcas submetidas ao SRE na maternidade. Teixeira et al (2004) igualmente obtiveram maior peso dos leitões ao desmame com o SRE.…”
Section: Resultsunclassified
“…Sow feed intake is one of the most important variables in lactation and must be constantly evaluated as it affects the availability of amino acids, which can determine whether a sow meets their nutritional requirements. It is influenced by sow parity (YOUNG et al, 2004), body composition (COOPER et al, 2001a), genetics (SAUBER et al, 1998, and environmental temperature (KIEFER et al, 2012). Currently, it is normal for lactating primiparous sows to achieve daily feed intake of less than the predetermined ideal values (COTA et al, 2003), and less than 18% of sows show the ideal pattern of feed intake during lactation (KOKETSU et al, 1996).…”
Section: Resultsmentioning
confidence: 99%